Targeting the PI3K/Akt/mTOR pathway with the pan-Akt inhibitor GDC-0068 in PIK3CA-mutant breast cancer brain metastases - Ippen, Franziska M.; Grosch, Julia Katharina (Neuro-Oncology, 2019)
AbstractBackground. Activating mutations in the pathway of phosphatidylinositol-3 kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) occur in 43-70% of bre
Gesehen am 30.01.2020